(untitled) (Research, Society and Development, 2023)
This work focuses on the concept of Buen Vivir related to Brazilian indigenous peoples. We seek to advance understandings of ways, expressions of life, and identity imbued with memory, ancestry, and historicity, but which at the same time point to alternative future perspectives. We carried out a bibliographic survey from August to September 2020, of articles published in Portuguese on the four main scientific platforms (SciELO, Scopus, Web of Science, and Scholar Google). We made a string search (bem viver and povos indígenas) and identified 18 publications that studied some aspect of the Buen Vivir of 37 ethnic groups. We systematized the studies according to the five elements: 1) view of the whole; 2) coexistence; 3) search for balance; 4) diversity; and 5) decolonization. We produced maps with the location of the studied ethnic groups, the watersheds covered and the distance from research centers, using Qgis free software. Although the North region of Brazil is home to more than 60% of Brazilian indigenous peoples, the results showed that the South and Southeast region account for 55% of the studies, and the Guarani ethnic group as the most studied. Accessibility to indigenous communities is a limiting factor for Buen Vivir studies in Brazil, only 5% of the indigenous communities mentioned were located more than 600 km from research centers. The most evident element of Buen Vivir was “A vision of the whole” for being the integrating element, followed by the elements “the search for balance” and “coexistence in multipolarity”. By highlighting these elements, we understand indigenous cosmovision as an important source of inspiration for (re)thinking about the contemporary civilization crisis.